Long-Term Effects of Activity Status in the Elderly on Cardiorespiratory Capacity, Blood Pressure, Blood Lipids, and Body Composition: A Five-Year Follow-Up Study - Eli Carmeli; Pini Orbach; David T. Lowenthal; Joav Merrick; Raymond Coleman (The Scientific World Journal)
It is generally recognized that physical activity levels in the elderly do not remain constant over time, and typically there is a marked reduction in physical activities in the elderly. The long-term benefits of regular physical training programs in the elderly are still not fully understood. This is a study of 55 elderly healthy subjects (over 65 years old) and re-evaluated for the effects of different physical activity patterns (sedentary, moderately active, and highly active) on several physiological parameters (pre- and post-training) after a 5-year period (5.30 ± 1.14 years). Measurements included: body composition, blood lipid profiles, resting systolic and diastolic blood pressure, maximal oxygen uptake, and pulmonary function. Results indicated a larger decrease in maximal oxygen uptake (VO2max) in the group of elderly sedentary individuals (1.5 ± 0.5 l/min) compared to the moderately active (1.7 ± 0.6 l/min) and the highly active groups (1.9 ± 0.4 l/min). An active lifestyle was not sufficient to increase the physiological function of an individual.This study could not clearly demonstrate favorable differences for the physically active groups over the sedentary group with regard to several important physiological factors over the 5-year follow-up and it appears that the recommendation for, and the initiation of, adopting active lifestyles may not be sufficient on their own to significantly increase an individual's physiological functioning.